Assessing Occupational Safety Culture and Climate through NOSACQ-50: A Case Study at PT Pertamina (Persero) Integrated Terminal Bitung - Papendang, Penris Sbarnan; Raton, Yulius Christian; Tumewu, Tryadi Wilhelmus (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Occupational safety is a crucial factor in maintaining operational continuity and employee well-being, particularly within the high-risk oil and gas industry. This study aims to evaluate the safety climate at PT Pertamina (Persero) Integrated Terminal Bitung using the Nordic Occupational Safety Climate Questionnaire (NOSACQ-50) instrument. A quantitative research approach with a survey design was employed, involving 79 respondents. Data were analyzed using the Mann–Whitney and Kruskal–Wallis tests to assess differences in perception among groups based on education level and length of employment. The results indicate that five out of seven safety climate dimensions fall within the “good” category, namely management commitment and competence in safety (3.49), management justice (3.32), worker commitment (3.25), learning, communication, and trust (3.34), and trust in the effectiveness of the safety system (3.33). The remaining two dimensions are categorized as “fair,” which include management safety empowerment (2.94) and safety priority and non-tolerance of risk (2.73).